Breaking Dormancy of Salak Seeds Using Various Concentration and Soaking Time of Gibberellins GA3 - Adrianton Adrianton; Jeki Jeki; Mustakim Mustakim; Farida Farida (Jurnal Penelitian Pendidikan IPA, 2024)
Dormancy is one of the obstacles in cultivating zalacca plants which have hard skin and seeds making them difficult to grow. Soaking using growth hormones is an alternative for growing seeds well. This research aims to determine the concentration of Gibberellin and determine the appropriate length of soaking time for Gibberellin (GA3) in germinating zalacca seeds. The research was carried out at the Seed Science and Technology Laboratory, Faculty of Agriculture, Tadulako University, Palu in January - February 2023 using a Completely Randomized Design with a factorial pattern. The first factor is the Gibberellin’s concentration which consists of 40, 60, and 80 ppm. The second factor was the length of Gibberellin’s soaking time which consists of 15, 55, and 95 minutes so that 9 treatment combinations were obtained which were repeated three times to obtain 27 experimental units. Each experiment used 20 seeds, therefore 540 zalacca seeds were needed, with 5 samples per experimental unit. The results show that gibberellin concentrations of 60 ppm and 80 ppm and soaking times of 55 and 95 minutes were treatments that provided good growth in germination capacity, germination time, plumule length, radicle length and dry weight of zalacca seed sprouts